Pengaruh Iklan Produk Baju di Shopee terhadap Minat Belanja Mahasiswa Jurusan Ilmu Komunikasi Kelas PR C Angkatan 2022 UIN Suska Riau - Darmawati Darmawati; Khofifah Amri (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study aims to determine the influence of clothing advertising on shopee on the shopping interest of PR C students of the Faculty of Communication Sciences UIN Susuka Riau class of 2022. The data analysis method used is simple linear regression using the SSPS program. Based on the results of data analysis, a correlation or relationship (R) value was obtained of 0.674 (67.4%). This value indicates that there is a strong correlation or relationship between advertising and interest. The results of the hypothesis test showed that the ttable > tcount was 5.075 > 2.039. Therefore, clothing advertisements on shopee have a significant influence on the purchase intention of students of the Communication Science Department of PR C class Class of 2022 UIN Suska Riau.